Public leadership in the United Arab Emirates: towards a research agenda. Issue 2 (6th March 2017) - Mathias, Megan
Abstract : Purpose: To date, public leadership has been conceptualised for Western systems while leadership discourse has spread across governments globally. The purpose of this paper is to begin the task of conceptualising public leadership in the United Arab Emirates (UAE), a federal monarchy in the Arabian Gulf, and proposes a forward research agenda. Design/methodology/approach: The paper employs a qualitative, interview-based design to elicit top government officials' personal interpretations of the purpose and challenges of public leadership, the practices they engage in, and the arenas across which leadership is performed. Findings: The study finds that whilst notions of public leadership as conceptualised to date are present, cultural and institutional differences result in distinct localised characteristics that belie the managerial presentation of public leadership. Stimulated by these initial findings, three points of departure for future research are suggested: public leaders' scope for discretion, values and trust. Research limitations/implications: The research relies on a relatively small, though élite, sample; findings are therefore preliminary, informing ideas for a forward research agenda. Originality/value: The paper presents a first conceptualisation of public leadership in the UAE, an Arab-Muslim federal monarchy.